2016
DOI: 10.1007/s10840-016-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mobility of the esophagus in patients undergoing catheter ablation of atrial fibrillation: data from computer tomography and 3D rotational angiography of the left atrium

Abstract: The most common position of the esophagus was behind the middle and left part of the LA. The outpatient views of the esophagus obtained before ablation did not reflect the position of the esophagus at the beginning of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…It is well known that the position of the esophagus to the left atrium is not stable but may change over time. Longterm mobility of the esophagus has been proven in several works comparing periprocedural 3DRA with a preprocedural CT of the heart 19, 20. Interesting result of our work is that the position of the esophagus before and after procedure is a relatively stable within a few hours of the ablation procedure.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is well known that the position of the esophagus to the left atrium is not stable but may change over time. Longterm mobility of the esophagus has been proven in several works comparing periprocedural 3DRA with a preprocedural CT of the heart 19, 20. Interesting result of our work is that the position of the esophagus before and after procedure is a relatively stable within a few hours of the ablation procedure.…”
Section: Discussionmentioning
confidence: 56%
“…The position of the esophagus from the CT of the heart have been described in a lot of works since 2004 15, 16, 17, 18. Some authors also proved longterm mobility of the esophagus comparing preprocedural CT of the left atrium and esophagus and 3DRA of the left atrium with esophagus imaging or contrast esophagogram during ablation procedure 6, 12, 19, 20. Two works with small group of patients assessed position of the esophagus from the 3DRA of the left atrium and esophagus6, 12 and data about mobility of the esophagus during ablation procedure are ambiguous 21, 22…”
Section: Introductionmentioning
confidence: 97%
“…An explanation could be the variability of the oesophageal position over time. Research in that field, in a small numbers of subjects, showed evidence for a fixed as well as a variable position [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of variability in the oesophageal position is still under debate. Research with small numbers of patients has provided evidence for a fixed as well as a variable position [21][22][23]33]. If the oesophageal position indeed has active dynamics, this could have affected our results.…”
Section: Study Limitationsmentioning
confidence: 93%
“…Nas regiões adjacentes aos limites das bordas do esôfago, evitam-se aplicações de RF56 . Desta forma, modificações da posição do esôfago durante o procedimento não serão identificadas e, também, poderá ser criada uma falsa impressão de segurança durante a aplicação da RF52,57 .Figura 10 -Sistema eletroanatômico 3D e fusão de imagens do AE e esôfago.Através do sistema de mapeamento eletroanatômico 3D e fusão de imagens do AE e do esôfago, que foram geradas pela RNM, foi possível delimitar as bordas laterais do esôfago através da marcação de pontos de cor amarela26 .Esta técnica pode ser realizada através da utilização de um termômetro esofágico ou por meio do uso de cateteres de eletrofisiologia os quais irão mostrar, de forma aproximada, o trajeto e bordas do esôfago.Também é possível utilizar um sistema de mapeamento eletroanatômico 3D que possibilita demarcar com pontos as bordas laterais do esôfago. Através do posicionamento de um cateter na luz esofágica e, que seja reconhecido pelo sistema de mapeamento eletroanatômico, é possível delimitar o trajeto estático do esôfago26 .A redução da energia aplicada na parede posterior do AE, com o intuito de reduzir o risco de lesões esofágicas térmicas é, provavelmente, a técnica mais utilizada.…”
unclassified